A valorização do professor do ensino médio em Santa Catarina e Minas Gerais: limites e possibilidades - Medeiros, Gilvan (2014)
The present study aimed to understand issues related to the valuation of high school teachers of Santa Catarina and Minas Gerais. To discuss this subject so dear to a quality education, were identified and analyzed journal articles related to the theme. The theoretical discussion was checked against data miners and teachers of Santa Catarina, extracted using the statistical software SPSS, mainly microdata School Census and PNAD (National Household Survey Sampling a), both from 2012. Was resorted also to statistical information of the subject teachers of high school of Santa Catarina and Minas Gerais database search "Teaching Work in Basic Education in Brazil." It was adopted as the axis of the valuation analysis of the high school teacher. Education of teachers of high school, career high school teacher and working conditions of the high school teacher: For this, the following content categories were treated. The study points to the limits and possibilities of exploitation of teachers surveyed states. There are challenges for the initial and continuing education, career, pay and working conditions. The analysis indicates problems of high school and their teachers, while pointing the challenges relating to education, career, pay and working conditions, and can contribute to the discussion on the definition of regular policies that meet the recovery teacher of high school. In this context, institutionalization is the core of the National System of Education as articulating element of a collective effort of federal entities, and the construction of a funding policy anchored in the perspective of quality public education. Such understanding should take into account the sanction made by the President of the Republic of Law. 13.005/2014 approving the National Plan of Education for the next decade.